The development of the new assistant practitioner role in the English National Health Service: a critical realist perspective. Issue 8 (12th August 2019) - Kessler, Ian; Spilsbury, Karen
Abstract: Adopting a critical realist perspective, this article examines the emergence of a relatively new non‐professional healthcare role, the assistant practitioner (AP). The role is presented as a malleable construct cascading through and sensitive to structure–agency interaction at different levels of NHS England: the sector, organisation and department. At the core of the analysis is the permissiveness of structures established at the respective levels of the NHS, facilitating or restricting agency as the role progresses through the healthcare system. A permissive regulatory framework at the sector level is reflected in the different choices made by two case study NHS acute hospital trusts, in their engagement with the AP role. These different choices have consequences for how the AP impacts at the departmental level.